FORM AND CONTENT FEATURES OF MODERN ENGLISH LITERATURE - Rzayeva Leyla Musa (Modern Scientific Technology, 2025)
Modern English literature has been shaped by socio-political, cultural and philosophical changes since the second half of the 20th century. The social and economic transformations that took place in Great Britain after World War II, the collapse of the empire and the process of globalization have given a new direction to literary thought. Modern writers now focus on the inner world of the individual, psychological states and identity problems, examining the interaction of man with society and technology. In terms of form, modern English literature has a fragmentary, polyphonic and experimental structure, moving away from the traditional plot line. Stream of consciousness, intertextuality, metanarrative approaches and intergenre synthesis are the main aesthetic principles of modern literature. These formal innovations turn the reader into an active participant, allow us to explore the semantic layers of the text and strengthen the interactive nature of literature. In terms of content, modern English literature reflects the psychological and existential dilemmas of the individual, experiences of alienation and loneliness, social inequality and class differences, postcolonial and multicultural experiences. Writers analyze the interaction between the internal and social realities of man, presenting both philosophical and aesthetic aspects in artistic form. Thus, modern English literature develops on the basis of the principle of unity of form and content and occupies a significant place in the global context of world literature. Studies show that this literature is a complex field of art with not only aesthetic, but also philosophical, psychological and social functions. The main purpose of the article is to systematically analyze the features of form and content in modern English literature, to reveal their mutual relationship and to study the leading aesthetic trends on a scientific-theoretical level. Historical-comparative, structural-semiotic and hermeneutic methods were used in the research process. The article also serves to determine the position of modern English literature in the world literary process